Exploiting altered patterns of choline kinase-alpha expression on human prostate tissue to prognosticate prostate cancer. Issue 9 (3rd June 2015) - Challapalli, Amarnath; Trousil, Sebastian; Hazell, Steve; Kozlowski, Kasia; Gudi, Mihir; Aboagye, Eric O; Mangar, Stephen
Abstract : Aims: Malignant transformation results in overexpression of choline-kinase (CHK) and altered choline metabolism, which is potentially detectable by immunohistochemistry (IHC). We investigated the utility of CHK-alpha (CHKA) IHC as a complement to current diagnostic investigation of prostate cancer by analysing expression patterns in normal (no evidence of malignancy) and malignant human prostate tissue samples. Methods: As an initial validation, paraffin-embedded prostatectomy specimen blocks with both normal and malignant prostate tissue were analysed for CHKA protein and mRNA expression by western blot and quantitative reverse transcriptase PCR (qRT-PCR), respectively. Subsequently, 100 paraffin-embedded malignant prostate tumour and 25 normal prostate cores were stained for both Ki67 (labelling-index: LI) and CHKA expression. Results: The validity of CHKA-antibody was verified using CHKA-transfected cells and siRNA knockdown. Immunoblotting of tissues showed good resolution of CHKA protein in malignant prostate, verifying use of the antibody for IHC. There was minimal qRT-PCR detectable CHKA mRNA in normal tissue, and conversely high expression in malignant prostate tissues. IHC of normal prostate cores showed mild (intensity) CHKA expression in only 28% (7/25) of samples with no Ki67 expression. In contrast, CHKA was expressed in all malignant prostate cores along with characteristically low proliferation (median 2% Ki67-LI; range 1–17%). Stratification of survival according to CHK intensity showed a trend towards lower progression-free survival with CHK score of 3. Conclusions: Increased expression of CHKA, detectable by IHC, is seen in malignant lesions. This relatively simple cost-effective technique (IHC) could complement current diagnostic procedures for prostate cancer and, therefore, warrants further investigation.